Risk of mortality in HIV-infected COVID-19 patients: A systematic review and meta-analysis - Tafadzwa Dzinamarira; Grant Murewanhema; Itai Chitungo; Bernard Ngara; Sphamandla Josias Nkambule; Roda Madziva; Helena Herrera; Solomon Mukwenha; Diego F. Cuadros; Patrick Gad Iradukunda; Moreblessing Mashora; Nigel Tungwarara; et al. (Elsevier, 2022)
Background: The relationship between HIV infection and COVID-19 clinical outcomes remains a significant public health research problem. We aimed to determine the association of HIV comorbidity with COVID-19 mortality. Methods: We searched PubMed, Google Scholar and World Health Organization library databases for relevant studies. All searches were conducted from 1st to 7th December 2021. Title, abstract and full text screening was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. The relative risk of mortality in HIV-infected COVID-19 patients was computed using a random-effects model. All analyses were performed using Meta and Metasens statistical packages available in R version 4.2.1 software package. The quality of included studies was assessed using the GRADE approach, Egger's test was employed to determine the risk of bias. Results: A total of 16 studies were included in this review. Among the COVID-19 patients with HIV infection, the mortality rate due to COVID-19 was 7.97% (4 287/53,801), and among the COVID-19 patients without HIV infection, the mortality rate due to COVID-19 was 0.69% (127, 961/18, 513, 747). In the random effects model, we found no statistically significant relative risk of mortality in HIV-infected COVID-19 patients (RR 1.07, 95% CI 0.86-1.32). The between-studies heterogeneity was substantial (I2 = 91%, P < 0.01), while the risk of publication bias was not significant. Conclusion: Findings did not link HIV infection with an increased risk of COVID-19 mortality. Our results add to the conflicting data on the relationship between COVID-19 and HIV infection.